Neutron measurements in radiotherapy: A method to correct neutron sensitive devices for parasitic photon response. (May 2017) - Irazola, L.; Terrón, J.A.; Bedogni, R.; Pola, A.; Lorenzoli, M.; Jimenez-Ortega, E.; Barbeiro, A.R.; Sánchez-Nieto, B.; Sánchez-Doblado, F.
Abstract: One of the major causes of secondary malignancies after radiotherapy treatments are peripheral doses, known to increase for some newer techniques (such as IMRT or VMAT). For accelerators operating above 10 MV, neutrons can represent important contribution to peripheral doses. This neutron contamination can be measured using different passive or active techniques, available in the literature. As far as active (or direct-reading) procedures are concerned, a major issue is represented by their parasitic photon sensitivity, which can significantly affect the measurement when the point of test is located near to the field-edge. This work proposes a simple method to estimate the unwanted photon contribution to these neutrons. As a relevant case study, the use of a recently neutron sensor for "in-phantom" measurements in high-energy machines was considered. The method, called "Dual Energy Photon Subtraction" (DEPS), requires pairs of measurements performed for the same treatment, in low-energy (6 MV) and high energy (e.g. 15 MV) fields. It assumes that the peripheral photon dose (PPD) at a fixed point in a phantom, normalized to the unit photon dose at the isocenter, does not depend on the treatment energy. Measurements with ionization chamber and Monte Carlo simulations were used to evaluate the validity of this hypothesis. DEPS method was compared to already published correction methods, such as the use of neutron absorber materials. In addition to its simplicity, an advantage of DEPs procedure is that it can be applied to any radiotherapy machine. Highlights: Correction of thermal neutron detectors for parasitic photon response. Peripheral photon dose study with distance in high and low energies in radiotherapy environments. Double energy photon subtraction methodology for reducing photon contribution in any thermal neutron detector.